2022
DOI: 10.1134/s0006297922070069
|View full text |Cite
|
Sign up to set email alerts
|

Semaphorin 3A in the Immune System: Twenty Years of Study

Abstract: Semaphorin 3A is a secreted glycoprotein, which was originally identifi ed as axon guidance factor in the neuronal system, but it also possesses immunoregulatory properties. Here, the eff ect of semaphorin 3A on T-lymphocytes, myeloid dendritic cells and macrophages is systematically analyzed on the bases of all publications available in the literature for 20 years. Expression of semaphorin 3A receptors -neuropilin-1 and plexins A -in these cells is described in details. The data obtained on human and murine c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 79 publications
(367 reference statements)
0
16
0
Order By: Relevance
“…It was reported that SEMA3A inhibits neutrophil migration, promotes a transition of classically activated (M1) macrophages toward a resolution phenotype and negatively regulates T-cell-mediated immune responses [ 22 , 23 , 24 ]. In patients with systemic lupus erythematosus reduced expression of SEMA3A correlated with inflammation and disease severity [ 25 ], and exogenous administration of SEMA3A was associated with markedly reduced articular inflammation in the rheumatoid arthritis mouse model [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…It was reported that SEMA3A inhibits neutrophil migration, promotes a transition of classically activated (M1) macrophages toward a resolution phenotype and negatively regulates T-cell-mediated immune responses [ 22 , 23 , 24 ]. In patients with systemic lupus erythematosus reduced expression of SEMA3A correlated with inflammation and disease severity [ 25 ], and exogenous administration of SEMA3A was associated with markedly reduced articular inflammation in the rheumatoid arthritis mouse model [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…The basic domain is located at the C-terminus of SEMA3A. The C-terminus determines its affinity to neuropilin-1 (NRP1) (Figure 1) [3,38]. SEMA3A has two receptors: NRP1 is necessary for ligand binding, while plexin A is important to subsequent signal transduction.…”
Section: Sema3a and Its Receptors And Its Expression In Kidneysmentioning
confidence: 99%
“…NRP1 is a transmembrane protein with a molecular weight of 120-130 kDa. The extracellular part contains three kinds of domains, made up of two complement binding domains a1/a2, two coagulation factor V/VIII domains, and a c-domain, and is connected to the NRP1 cytoplasmic part (Figure 1) [3]. The signaling receptor Plexin A is a transmembrane glycoprotein with a SEMA3A-like extracellular part, which, implying their common evolutionary origin, is followed by three PSI domains and three IPT (Ig-like, plexins and transcription factors) domains.…”
Section: Sema3a and Its Receptors And Its Expression In Kidneysmentioning
confidence: 99%
See 2 more Smart Citations